Análise das reações entre as características da estrutura organizacional e o nível de desenvolvimento dos processos gerenciais de empresas de construção civil - Yuki, Wagner Shigueo (2011)
This research is an exploratory study on the analysis of relations between the organizational structure characteristics and level of development of the management processes of construction companies. The review was based on the theory of organizations, organizational maturity models, Porter's five forces model and PCF (Process Classification Framework). Data were collected through a questionnaire administered to construction professionals. The consolidation was performed with software Predictive Analytics Software - SPSS (old SPSS) through the analysis of Pearson and canonical correlation. Research has shown that there is a correlation between levels of development of management processes in companies interviewed and their organizational structure and also the characteristics identified which directly interfere the management of construction companies. The Pearson analysis provided a correlation between each variable with another and the canonical correlation analysis allowed the correlation of the two groups by means of the canonical functions. This research contributed to a better understanding of management processes in construction companies, and organizational structure.